Kedudukan Perjanjian Internasional Bagi Indonesia Berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Dan Undang-Undang Nomor 24 Tahun 2000 Tentang Perjanjian Internasional - Dian Alya; Yolanda Fitri; Windia Febrica Stevany; Ema Septaria; M. Ilham Adepio (GLOBAL SCIENTS PUBLISHER, 2026)
The development of globalization has increased Indonesia’s involvement in international treaties, creating the need for legal certainty in their implementation at the national level. This study aims to analyze the position of international treaties within the Indonesian legal system based on the 1945 Constitution of the Republic of Indonesia and Law Number 24 of 2000 concerning International Treaties. The research method used is normative juridical with statutory and conceptual approaches. The results show that international treaties have a constitutional basis in Article 11 of the 1945 Constitution and require ratification to be applicable in national law, reflecting a moderate dualism approach. However, their position within the hierarchy of laws and regulations is not explicitly regulated, which may lead to normative conflicts. Furthermore, constitutional supremacy remains the fundamental principle in Indonesia’s legal system.